Insights into the respective role of acidification and oxidation for enhancing anaerobic digested sludge dewatering performance with Fenton process. (April 2015) - Zhang, Weijun; Yang, Peng; Yang, Xiaoyin; Chen, Zhan; Wang, Dongsheng
Graphical abstract: Highlights: Proteins were effectively removed from sludge bulk after acidification treatment. Acidification and Fenton oxidation showed a significant synergetic effect. Oxidation played a more important role than coagulation in Fenton conditioning. Extracellular polymers degradation was the major mechanism of sludge conditioning. Abstract: Digested sludges generally exhibit poorer dewaterability than activated sludges. This study investigated the effects of acidification and oxidation on EPS properties and dewaterability of anaerobic digested sludge in Fenton treatment in order to unravel the underlying mechanism of sludge conditioning. The results indicated that sludge dewatering property was improved after acidification treatment. Meanwhile, fluorescence analysis revealed that the protein-like substances were effectively removed from sludge bulk after acidification treatment. Acidification and Fenton oxidation showed a significant synergetic effect in enhancing sludge dewatering process. Solubilization and decomposition of bound EPS occurred synchronously during Fenton conditioning. Oxidation process is very likely to play a more important role in sludge conditioning than Fenton coagulation. According to pilot test, Fenton treatment performed much better in cake moisture content reduction than chemical conditioning with traditional inorganic coagulants. Additionally, full-scale application of Fenton conditioning will not have detrimental effects on performance of wastewater treatment system.